Carotenoids Functionality, Sources, and Processing by Supercritical Technology: A Review - Natália Mezzomo; Sandra R. S. Ferreira (Journal of Chemistry)
Carotenoid is a group of pigments naturally present in vegetal raw materials that have biological properties. These pigments have been used mainly in food, pharmaceutical, and cosmetic industries. Currently, the industrial production is executed through chemical synthesis, but natural alternatives of carotenoid production/attainment are in development. The carotenoid extraction occurs generally with vegetal oil and organic solvents, but supercritical technology is an alternative technique to the recovery of these compounds, presenting many advantages when compared to conventional process. Brazil has an ample diversity of vegetal sources inadequately investigated and, then, a major development of optimization and validation of carotenoid production/attainment methods is necessary, so that the benefits of these pigments can be delivered to the consumer.